"To Render Prompt Justice": The Origins and Construction of the U.S. Court of Claims. Issue 2 (October 2022) - Dichio, Michael; Strother, Logan; Williams, Ryan J.
Abstract: This article examines the institutional development of the U.S. Court of Claims (USCC), in order to shed new light on the nature of constitutional and institutional change in the early Republic. From the founding period through the mid-nineteenth century, members of Congress believed that empowering other institutions to award claimants monies from the Treasury would violate two core doctrines: separation of powers and sovereign immunity. However, as claims against the government ballooned over the first half of the nineteenth century, Congress fundamentally changed its interpretation of the Constitution's requirements in order to create the USCC and thus to alleviate its workload. This story of institutional development is an example of constitutional construction and creative syncretism in that the institutional development of the USCC came from continuous interactions among political actors, working iteratively to refashion institutions capable of solving practical problems of governance. This close study of the court's creation shows something important about American constitutional development: Certain fundamental ideas of the early Republic, including sovereign immunity and separation of powers, were altered or jettisoned not out of some grand rethinking of the nature of the American state, but out of the need to solve a mundane problem.